TO ASSESS THE KNOWLEDGE, ATTITUDE, AND PRACTICE OF PHARMACOVIGILANCE AND ADVERSE DRUG REACTION REPORTING AMONG THE UNDERGRADUATE AND POSTGRADUATE MEDICAL STUDENTS IN A TERTIARY CARE TEACHING HOSPITAL IN ASSAM: A QUESTIONNAIRE-BASED STUDY - Singh, S Renuka; Khanikar, Dwipen; Saikia, Pran Pratim; Devi, Diptimayee (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: Adverse drug reaction (ADR) is an important factor contributing to mortality and morbidity worldwide. Since undergraduate (UG) and postgraduate (PG) students are the future caregivers to the patients, they should have sound knowledge, a positive attitude, and good practice of Pharmacovigilance (PV). Hence this study was conducted to assess their knowledge, attitude, and practice (KAP) of PV and ADR reporting. Furthermore, secondarily this study tried to look into the impact of competency-based medical education (CBME) on the KAP of the students. Methods: Questionnaire-based, observational, and cross-sectional study. The questionnaire was pre-validated and consisted of 30 questions to assess the KAP of UG and PG medical students of a tertiary care teaching hospital in Assam. Results: A total of 419 students participated in the study. Data were analyzed using Microsoft Excel Sheet and the Student’s t-test. Both UGs and PGs have good knowledge about PV, ADR, and the types of ADRs to be reported. They also have a positive attitude but in practice, only a few have filled up the ADR form. Mean score analysis showed p-value was significant for attitude and practice among the UGs and PGs and highly significant for KAP when the CBME and Old Curriculum were compared. Conclusion: Although students have good knowledge and attitude, they need to improve in their practice. Regular training and awareness programs might help in educating them about PV and ADR reporting. However, the introduction of the CBME curriculum has been shown to improve the knowledge and attitude of the students about PV and ADR reporting.